Cover Picture: Discovery of MK‐8970: An Acetal Carbonate Prodrug of Raltegravir with Enhanced Colonic Absorption (ChemMedChem 2/2015). Issue 2 (February 2015) - Walji, Abbas M.; Sanchez, Rosa I.; Clas, Sophie‐Dorothee; Nofsinger, Rebecca; de Lera Ruiz, Manuel; Li, Jing; Bennet, Amrithraj; John, Christopher; Bennett, David Jonathan; Sanders, John M.; Di Marco, Christina N.; Kim, Somang Hope; et al.
<x xml:space="preserve">Abstract</x> The front cover picture shows raltegravir, a safe and efficacious HIV integrase strand‐transfer inhibitor marketed for the treatment of HIV/AIDS under the name Isentress®, in complex with the prototype foamy virus (PFV) intasome. MK‐8970 is an acetal carbonate prodrug of raltegravir, specifically designed to enhance colonic absorption after oral dosing and maintain inhibition of HIV integrase to enable once‐daily dosing. For further details, see the Full Paper by Abbas M. Walji et al. on p. 245 ff. Coordinates for the raltegravir–PFV intasome complex were taken from PDB ID 3OYA (S. Hare, S. S. Gupta, E. Valkov, A. Engelman, P. Cherepanov, Nature 2010, 464, 232–236). The cover art was produced in conjunction with Sharon O'Brien (Merck Creative Services).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>